Risk analysis of tender failure in the procurement of construction services - Janita, Andreana; Dwi Hatmoko, Jati Utomo; Hermawan, Ferry (Jurnal Teknika, 2023)
Failed tender often occurs in the process of procuring in government agencies. In BP2JK Central Java, the number of failed tender packages in the last 3 years is quite high, namely 10-35%. This study aims to analyze the risk of failed tender in the BP2JK area. The method used in this study is descriptive quantitative, where the analysis was based on historical procurement data in the last 4 (four) years and also on a questionnaire to 90 respondents consisting of 28 Pokja and 62 PPK in the BP2JK Central Java area. The results of the analysis show that there are 12 identified risks. If sorted from the highest risk level, these include: selection document errors, evaluation process errors, procurement implementation that was not on schedule, no participants passed the evaluation, bids did not meet requirements, procurement process errors, more than 1 (one) document uploaded, overqualified, owner estimate too low, participants did not show evidence, e-procurement system was hacked and price negotiations were not reached. While the method was frequently used as a risk response is reducing the possibility of a risk occurring, and followed by reducing the impact of risk, sharing risk, avoiding risk or accepting risk.